The ferrite resonator in rectangular waveguide with transverce magnetic field - Шматько, А. А.; Мизерник, В. Н.; Одаренко, Е. Н. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”)
The analysis natural and forced oscillations of the ferrite resonator in a rectangular wave guide with a traversal magnetic field on the basis of the gained rigorous analytical solution of a boundary electrodynamic problem is lead. Existence of several modes of oscillations of the ferrite resonator is erected: a mode on the ungated volumetric modes and a mode on the ungated surface modes with material roots of the dispersion equation and a mode on leaking modes with complex roots of the dispersion equation. For forced oscillations analytical expressions for reflectivities and passage waveguide waves are found. It is shown, that changing quantity of an effective magnetic conductivity of ferrite due to a magnetic field it is possible to provide the full passage or reflection waveguided waves in frequency broadband.